Development of an Enzyme-Linked Immunosorbent Assay for Cyhalothrin. (August 2013) - Chen, Xiujin; Xu, Liguang; Ma, Wei; Liu, Liqiang; Kuang, Hua; Peng, Chifang; Wang, Libing; Xu, Chuanlai
Abstract : In the present study, we obtained a specific monoclonal antibody (cross-reaction to analogues <5%) against cyhalothrin using two haptens. After 7 reaction steps, 3-cyano-[(cis)-3-(2-chloro-3, 3, 3-trifluoroethenyl-2, 2-dimethyl)-cyclopropane-carbonyloxy]-phenoxybenzyl propanoic acid was prepared with yield 35.9%. Four coating antigens and two immunogens were prepared. A heterologous enzyme-linked immunosorbent assay for cyhalothrin was established with the 50% inhibition concentration (IC50, 13.26 ± 1.23 ng mL −1 ) after optimizing various parameters including coating antigens, blocking agents, ionic strength, pH value and methanol concentration in the assay buffer. To evaluate the proposed immunoassay, spiked samples from river, tap water and drinking water at three levels (0.2,  1.0,  5.0 mg L −1 ) were tested after simple dilution. The mean recoveries ranged from 75.4% to 97.7% with coefficient of variation 5.1%–11.6%. The results from the above indicated the potencies of this ELISA in cyhalothrin analysis.